SOFTWARE VOLTAGE REGULATION ON TIRE OF TRACTION SUBSTATION - Sychenko, V. H.; Bader, M. P.; Havryliuk, V. I. (Science and Transport Progress, 2005)
The criteria of voltage regulating quality on tractive power supply substation buses have been analyzed and the suboptimum adaptive algorithm of voltage regulation has been proposed. The method developed for a Dcelectrified railway section allows reducing maintenance costs and does not require significant expenses for its implementation.